Contrasting response of water use efficiency to soil moisture availability: From leaf to ecosystem in an arid oasis. (March 2023) - Han, Tuo; Feng, Qi; Yu, Tengfei; Liu, Wei; Ma, Jinzhu; Zhao, Chenguang; Yang, Linshan; Zhang, Jutao; Li, Huiying
Graphical abstract: Abstract: Water availability profoundly and simultaneously affects the water cycle and disturbs terrestrial carbon cycle. However, there is currently a lack of knowledge about how carbon–water coupling occurs in response to soil moisture availability, and the underlying mechanisms. Here, using two kinds of observational datasets ( i.e ., leaf gas exchange and ecosystem eddy-covariance), we evaluated a normalized water-use efficiency (WUE) measure ( g 1, the "stomatal conductance slope"), and explored its dynamic behavior in response to soil moisture availability. It was found that patterns of seasonal variations in WUE were not consistent between the two datasets. A contrasting response of G1 (the capital letter denotes g 1 at the ecosystem level) to volumetric water content ( VWC ) during different stages of the growing season was confirmed, which was attributed to the different sensitivities of biological processes (i.e., photosynthesis and transpiration) to soil moisture availability. WUE variability during the main growing seasons was primarily controlled by transpiration, whereas WUE variability during the early and late growing seasons was mostly controlled by photosynthesis. Our findings suggest that phenology plays a significant role in regulating carbon–water coupling processes, and then exerts biotic control. The insights gained from this study will facilitate an in-depth understanding of the responses of plant biological processes to global change.